Defining Religion: New patterns of political governance in Catalonia and Spain - Griera, Maria (Eurostudia)

(untitled) (Le Centre canadien d'études allemandes et européennes, 2008)
AbstractHistorically in Spain policies to govern religion have been undertaken and controlled by the central state. After the end of the Franco era and especially since the early nineties there have been significant changes in this field. The article therefore distinguishes two main patterns of regulation of religious matters: the first of these patterns can be described as a top-down political program of government and the second one as a bottom-up policy process of governing religious diversity. The first is mainly based on the application of the “church-state” model to the regulation and control of religious minorities. The second is a new pattern which promotes a different way of dealing with religious minorities being greatly influenced by the proposals of interfaith groups and multicultural theories. It initially appeared in Catalonia and slowly develops in whole Spain. However both patterns are not completely independent; current developments in both are rather influenced by one another.